Optimal Control Strategies for Adaptive Pricing in Ride-Sharing Services - Mejjaouli, Sobhi; Tadj, Lotfi (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
Rideshare platforms are an example of economies of sharing where ride requests initiated by riders are fulfilled by car owners through the platform that connects both of them. When demand for a ride is initiated by the customer, the platform checks service providers’ (car owners) availability and assigns a fare (ride price) that both the ride requester and provider should agree on to complete the transaction, and the ride service is fulfilled. In this research, optimal pricing strategies for ride-share platforms are considered. The optimal control approach is used to first develop differential equations to model the dynamics of the number of ride requests and for the price rate. Second, we model the total profit as a function of a linear revenue and a nonlinear cost. The optimal rate of change in the ride price is then obtained. Finally, a numerical example and extensive sensitivity analyses not only provide insights into the effect of the system parameter on the model but also lead to managerial implications to help companies determine the best price for each ride.